Nutritional Status of Children Under the Age of Five Years in Pakistan - Zahid Mahmood, Junaid Ghaffar, Khalid Mahmood, Muhammad Uzair, Riffat Farrukh, Shaheen Masood, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Malnutrition has become quite common among children especially in rural areas of Pakistan. The nutritional status of children under the age of five was assessed and the degree of malnutrition and its associated factors were studied. The socioeconomic status, delayed weaning and lack of education of parents are some of the key reasons of malnutrition in case of children. Objectives: This study aimed to analyze the nutritional status of children under the age of five years in Pakistan Study design: This is a cross-sectional study conducted on 250 children that visited the tertiary care center Shaikh Zayed Hospital, Rahim Yar Khan and Abbasi Shaheed Hospital, Karachi from May 2021 to April 2022.The study duration was one year. Materials and methods: The data was taken from 250 children, among these there were 147 boys and 103 girls. Written consent was taken from the parents, and they were fully aware of the study. The children were selected as per Non-probability convenient sample method. The physical growth and nutritional condition was evaluated by making use of basic anthropometric technique. A semi-structured questionnaire was prepared and face to face interview was carried out with the mothers of the children. SPSS version 16 was used for calculations and statistical analysis was done by using the same software. Results: Out of 250 children that were included in the study, 147 were boys and 103 were girls. By using the Gomez classification, the degree of malnutrition was analyzed among the children. It was observed that 150 children were facing malnutrition. 28% of the cases had first degree malnutrition, 14% and 17% had second and third degree condition. Stunted growth was observed in 130 children. There were 285 children with mild stunted growth; however 8% and 11% had moderate and severe form of stunted growth problem. Lack of education of mothers was seen to be directly linked with malnutrition in this study. Conclusion: Health education about proper breast feeding and immunization of children should be provided to the parents to prevent malnutrition among children. Keywords: Nutritional status, Risk factors, Child, Malnutrition